ANALYSIS OF ISLAMIC VALUES INTEGRATION THROUGH TEACHERS' LESSON PLAN IN CLASSIFICATION OF LIVING THINGS TOPIC - Shafa Namira Nur Rachmadewi, - (2022)
The efforts to integrate Islam and science learning have been found in several educational institutions in Indonesia lately. Classification of living things is a topic learned in natural science by students in grade seven (VII) based on National Curriculum (K-13). The purpose of this study is to analyze the Islamic values integration towards science learning through teachers' lesson plan in classification of living things topic. This study used descriptive method to examine the situation in natural condition. Populations of this research are documents of science teachers' lesson plan in classification of living things topic grade seven (VII) from private Islamic junior high school in Bandung Raya with the sample are 40 lesson plans that come from 9 private Islamic junior high school. Lawshe's CVR (Content Validity Ratio) is used to test the validity and reliability of the instrument being used in this research. Based on the findings, the pattern of Islamic values integration in learning objectives is shown in the form of sources of values in Islam, categories of values in Islam, and nafsiyah. The pattern of Islamic values integration in opening activity is indicated by nafsiyah, categories of values in Islam, sources of values in Islam and interconnection-integration. The pattern of Islamic values integration in core activity is shown by sources of values in Islam, iqra, hiwar, nafsiyah, and interconnection-integration. The pattern of Islamic values integration in closing activity is indicated by categories of values in Islam along with targhib and tarhib. Upaya mengintegrasikan pembelajaran Islam dan sains telah ditemukan di beberapa lembaga pendidikan di Indonesia akhir-akhir ini. Klasifikasi makhluk hidup merupakan topik yang dipelajari dalam mata pelajara IPA oleh siswa kelas VII berdasarkan Kurikulum Nasional (K-13). Tujuan penelitian ini adalah untuk menganalisis integrasi nilai-nilai Islam terhadap pembelajaran IPA melalui Rencana Pelaksanaan Pembelajaran (RPP) mata pelajaran klasifikasi makhluk hidup. Penelitian ini menggunakan metode deskriptif untuk mengkaji situasi yang terjadi sebenarnya di lapangan. Populasi dalam penelitian ini adalah dokumen RPP guru IPA mata pelajaran klasifikasi makhluk hidup kelas VII (VII) SMP Islam swasta di wilayah Bandung Raya dengan sampel 40 RPP yang berasal dari 9 SMP Islam swasta di wilayah Bandung Raya. CVR (Content Validity Ratio) Lawshe digunakan untuk menguji validitas dan reliabilitas instrumen yang digunakan dalam penelitian ini. Berdasarkan temuan, pola integrasi nilai-nilai Islam dalam tujuan pembelajaran ditunjukkan dalam bentuk sumber nilai dalam Islam, kategori nilai dalam Islam, dan nafsiyah. Pola integrasi nilai-nilai Islam dalam kegiatan pembukaan ditunjukkan dengan nafsiyah, kategori nilai dalam Islam, sumber nilai dalam Islam dan interkoneksi-integrasi. Pola integrasi nilai-nilai Islam dalam kegiatan inti ditunjukkan oleh sumber-sumber nilai dalam Islam, iqra, hiwar, nafsiyah, dan interkoneksi-integrasi. Pola integrasi nilai-nilai Islam dalam kegiatan penutup ditunjukkan dengan kategori-kategori nilai dalam Islam beserta targhib dan tarhib.